2007
DOI: 10.4049/jimmunol.178.5.3186
|View full text |Cite
|
Sign up to set email alerts
|

TLR9 Expression and Function Is Abolished by the Cervical Cancer-Associated Human Papillomavirus Type 16

Abstract: Cervical cancer development is linked to the persistent infection by high-risk mucosal human papillomaviruses (HPVs) types. The E6 and E7 major oncoproteins from this dsDNA virus play a key role in the deregulation of the cell cycle, apoptosis, and adaptive immune surveillance. In this study, we show for the first time that HPV type 16 (HPV16), the most carcinogenic type among the high-risk subgroup, interferes with innate immunity by affecting the expression of TLRs. Infection of human primary keratinocytes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
311
0
26

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 323 publications
(359 citation statements)
references
References 78 publications
(64 reference statements)
22
311
0
26
Order By: Relevance
“…THP-1 cells were transfected with the Ϫ3496 TLR8 promoter cloned in front of the luciferase (Luc) reporter gene. Cells were harvested as described previously (19). The data are the mean of three independent experiments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…THP-1 cells were transfected with the Ϫ3496 TLR8 promoter cloned in front of the luciferase (Luc) reporter gene. Cells were harvested as described previously (19). The data are the mean of three independent experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Monocytes were purified from peripheral blood mononuclear cells using CD14-positive selection (Miltenyi) and cultured as described previously (18). Huh-7 cells (kindly provided by Alex Weber, Deutsches Krebsforschungszentrum) and HEK293 were grown in the same conditions as described previously (19). Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[40][41][42] HPV 16 E5 interacts with HLA I heavy chain preventing transport of the major histocompatibility class I (MHC I in mice; HLA class I in humans) to the cell surface. 43 The E5 expression was accompanied by a decreased expression of HLA-A2 and had a functional impact on recognition of E5 expressing cells by HPV specific CD81 T cells.…”
Section: Discussionmentioning
confidence: 99%
“…The E6 and E7 oncoproteins exert their functions by inducing the degradation of two important tumor suppressors, p53 and retino-blastoma (pRb), respectively, and cooperates with each other to immortalize primary keratinocytes (Stanley et al, 2007). However, Hasan UA (Hasan et al, 2007) found that TLR9 expression and function also was abolished by the cervical cancer-associated human papillomavirus type 16.…”
Section: Tlr9 Expression In Uterine Cervical Lesions Of Uyghur Women mentioning
confidence: 99%